A case study investigating the essay writing skills of Eastern Cape Technikon education students using the Writing Process Workshop language software - Masha, Khanyisa Rose (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2005.